A companion to ancient aesthetics - Destrée, Pierre (Blackwell companions to the ancient world., 2015)
The first of its kind, A Companion to Ancient aesthetics presents a synoptic view of the arts, which crosses traditional boundaries and explores the aesthetic experience of the ancients across a range of media-oral, aural, visual, and literary.-Investigates the many ways in which the arts were experienced and conceptualized in the ancient world -Explores the aesthetic experience of the ancients across a range of media, treating literary, oral, aural, and visual arts together in a single volume -Presents an integrated perspective on the major themes of ancient aesthetics which challenges traditional demarcations -Raises questions about the similarities and differences between ancient and modern ways of thinking about the place of art in society.